Gut Microbiota in Postpartum Depression: Pathogenesis and Treatment Perspectives - a review - Czerepak, Irmina; Kapij, Marcin; Bochenek, Hubert; Bzoma, Michał; Gugulska, Julia; Bielicka, Anna; Szwarc, Tomasz; Komasara, Piotr; Niewczas, Karolina; Brzozowska, Adrianna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Postpartum depression (PPD) is a prevalent and serious mood disorder following childbirth, affecting approximately 10-20% of new mothers worldwide. PPD not only impacts a mother’s mental health but also her relationship with her infant, her family, and the psychosocial development of the child. While numerous factors (genetic, hormonal, psychosocial, immunological) contribute to its pathogenesis, growing evidence underscores the central importance of the gut-brain axis and gut microbiota dysbiosis. This article aims to summarise current knowledge on crucial role of gut microbiota in the onset, progression and therapeutic possibilities of PPD. Description of the state of knowledge: Gut microbes influence PPD through the gut-brain axis, impacting neuroendocrine systems, immune responses, and neurotransmitter production. In particular, alterations in gut microbiota composition such as reduced levels of short-chain fatty acid-producing bacteria and an increased abundance of pro-inflammatory taxa have been linked to immune dysregulation, heightened stress responses, and altered neurotransmitter metabolism in PPD. Studies show that microbial dysbiosis correlate with PPD symptoms, while interventions like probiotics and dietary changes offer promising therapeutic avenues. Summary: This review summarizes current evidence on the gut–brain axis in depression, observed gut microbiota changes in PPD, mechanistic pathways linking dysbiosis to postpartum mood disturbances, and emerging microbiota-targeted therapies, including probiotics and fecal microbiota transplantation (FMT).